PEGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF DAN GAYA BELAJAR KOGNITIF TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL - Nursanita Nasution; Acep Nurulah (Akademika, 2017)
This study aims to determine the effect of cooperative learning models and studentlearning styles on the results of learning Social Sciences. Conventional learning models thatrely on reading books, multiplying practice exercises, teacher explanations in the classroom,students are expected to be more diligent in practicing questions suspected of influencingsocial studies learning outcomes. Conventional models are considered to be less than optimal,because basically students will easily feel bored because they have to open sheets per sheetby understanding the contents of the book and listening to the teacher's explanation in frontof the class verbally.This study uses an experimental comparison method containing activities planned and carriedout by researchers, 2x2 factorial design in this study to find out whether there are differencesin social studies learning outcomes between students who obtain learning with cooperativelearning models and students who obtain conventional learning. The population in this studywere all eighth grade students of Al-Kamil Middle School Islamic Boarding School in CianjurRegency, West Java. Affordable population there are eighth grade students of Al-KamilMiddle School Islamic Boarding School District. Cianjur numbered 120 students. The resultsof this study indicate that there is an interaction effect between learning models and learningstyles on the results of social studies learning at Al-Kamil Middle School Islamic BoardingSchool. Learning outcomes of students who have independent learning styles and followcooperative learning models are higher than students' learning outcomes that followconventional learning models. Likewise the learning outcomes of students who havedependent learning styles and follow cooperative learning models are higher than students'learning outcomes that follow conventional learning models